2007
DOI: 10.1111/j.1872-034x.2007.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection in hepatic encephalopathy: Relationship to plasma endotoxins and blood ammonia

Abstract: In conclusion, we submit that H. pylori infection might, in fact, play a role in increasing the circulating levels of ammonia and endotoxins in cirrhotic patients, thus facilitating the onset of HE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…We have previously reported that ammonia level in portal vein blood of cirrhotic patients with H pylori infection is significantly higher than that in patients without infection [22] . In the present study, HE was more frequently observed in patients with H pylori infection than in those without (58.5% vs 30.6%, P < 0.01), which was consistent with that reported elsewhere [23][24][25] .The hypothesis that H pylori infection plays a pathogenic role in HE was initially devised by Gubbins et al [26] . In their study, seroprevalence for H pylori was detected in 78.6% of 117 alcoholic liver disease patients with HE, and in 62% of 71 patients without (P = 0.013).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We have previously reported that ammonia level in portal vein blood of cirrhotic patients with H pylori infection is significantly higher than that in patients without infection [22] . In the present study, HE was more frequently observed in patients with H pylori infection than in those without (58.5% vs 30.6%, P < 0.01), which was consistent with that reported elsewhere [23][24][25] .The hypothesis that H pylori infection plays a pathogenic role in HE was initially devised by Gubbins et al [26] . In their study, seroprevalence for H pylori was detected in 78.6% of 117 alcoholic liver disease patients with HE, and in 62% of 71 patients without (P = 0.013).…”
Section: Discussionsupporting
confidence: 82%
“…Although the pathogenesis is unclear, ammonia is one of the key factors involved. Recently, it has been suggested H pylori contributes to hyperammonemia in cirrhosis, and bacterium eradication decreases blood ammonia concentration in these patients [1][2][3][4][5][6][7][8] . However, the literature contains conflicting data, with several other studies showing ammonia levels do not significantly differ between cirrhotic patients with and without H pylori infection.…”
Section: Introductionmentioning
confidence: 99%
“…26 Previous studies have described glycogen depletion in various infectious and pathological conditions, although the mechanism of depletion of liver glycogen stores in endotoxemia is still unclear. 27 Histological findings in this study suggest a possible derangement of carbohydrate metabolism in rodents infected with H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…It has been supposed that H pylori may increase blood ammonia concentration and induce HE when the bacterium is widely distributed in the stomach, and in the presence of severe liver impairment (Child-Pugh class B or C) with abundant hepatic bypass. Some studies showed that hepatic encephalopathy patient with hyperammonaemia that was controlled by eradication of H. pylori (4). Other studies revealed that the prevalence of H. pylori in liver cirrhosis patients was similar to that in controls and no correlation was found between gastric and blood ammonia levels.…”
Section: Introduction:-mentioning
confidence: 98%
“…There are many factors responsible for the development of HE in liver cirrhosis such as: ammonia, production of false neurotransmitters, increase sensitivity of central nervous system neurons to the inhibitory neurotransmitters Gamma Amino Butyric Acid (GABA), increased level of circulating endogenous benzodiazepines, decreased activity of urea-cycle enzymes due to Zinc deficiency, decreased level of myoinositol in brain, deposition of manganese in basal ganglia and swelling of brain astrocytes (4). Ammonia is a substance most often incriminated in the pathogenesis of encephalopathy; Most of the ammonia is of gut origin where it is produced by the bacterial flora and when stomach infected with Helicobacter pylori (H. pylori) it is postulated that it is an additional source of ammonia production.…”
Section: Introduction:-mentioning
confidence: 99%